Analysis of the Profile of Bullying Perpetrators - Crusita Widya Anggraeni; Nono Hery Yoenanto (Psikostudia : Jurnal Psikologi, 2025)
Bullying in the educational context has serious impacts on the psychological and social well-being of victims, while also creating an unsafe learning environment. Despite extensive research on bullying, there is a gap in understanding the perpetrators, particularly in the educational context. This study employs the Systematic Literature Review (SLR) method to identify and summarize previous research findings regarding the profile of bullying perpetrators. From the 11 articles analyzed, this study reveals various factors influencing the behavior of bullying perpetrators, including a lack of empathy, low empathy skills, and the absence of preventive procedures in schools. The perpetrators' perceptions of their actions, involving elements of humor or self-satisfaction, are also crucial aspects to understand. The profile of bullying perpetrators includes personality characteristics, low empathy skills, and emotional issues such as anger and satisfaction after committing bullying acts. External factors such as family environment, leisure activities, and emotional conditions also influence the perpetrators' behavior. This study provides insights into the complexity of bullying perpetrators in the educational context. It highlights the importance of understanding the impact of bullying on all parties involved, with the hope of making a significant contribution to creating a safe, supportive, and bullying-free educational environment. Bullying dalam konteks pendidikan menimbulkan dampak serius pada kesejahteraan psikologis dan sosial korban, sambil menciptakan lingkungan belajar yang tidak aman. Meskipun telah banyak penelitian tentang bullying, terdapat kesenjangan dalam pemahaman tentang pelaku, khususnya dalam konteks pendidikan. Penelitian ini menggunakan metode Systematic Literature Review (SLR) untuk mengidentifikasi dan merangkum hasil penelitian sebelumnya mengenai profil pelaku bullying. Dari 11 artikel yang dianalisis, penelitian ini mengungkapkan berbagai faktor yang memengaruhi perilaku pelaku bullying, kurangnya empati, kemampuan empati yang rendah, dan kekurangan prosedur pencegahan di sekolah. Persepsi pelaku terhadap tindakan mereka, yang melibatkan aspek humor atau kepuasan diri, juga menjadi elemen penting yang perlu dipahami. Profil pelaku bullying mencakup karakteristik kepribadian, rendahnya kemampuan empati, serta masalah emosional seperti rasa marah dan kepuasan setelah melakukan tindakan bullying. Faktor eksternal seperti lingkungan keluarga, aktivitas waktu luang, dan kondisi emosi juga mempengaruhi perilaku pelaku. Penelitian ini memberikan wawasan tentang kompleksitas pelaku bullying dalam konteks pendidikan. Penelitian ini menyoroti pentingnya memahami dampak bullying pada semua pihak terlibat, dengan harapan dapat memberikan kontribusi signifikan untuk membangun lingkungan pendidikan yang aman, suportif, dan bebas dari perilaku bullying.